Human Capital Investment And Training In Islamic Banking Industry In Jordan Jordan Islamic Bank for Finance and Investment - Ziad Mohammad Obeidat (European Scientific Journal, ESJ, 2016)
The purpose of this study is to measure the impact of investment in human resources activities on the effectiveness of investment in human capital and investigated the relationship between human capital Investmenttraining and its effectiveness in Islamic banks in Jordan. The fascinating development and point of discussion in recent years is the rapid growth and expansion of the Islamic financial services industry. It is no longer rhetoric as Islamic finance has been accepted as viable and competitive mode of financial intermediation that offers wide range of financial products and services to meet the highly differentiated demands of the new economy; not only in Muslim countries but also beyond the Muslim world. Against these rapid revolution of Islamic financial industry globally and in Jordan particularly, human capital has become the defining factor in sustaining the performance and competitiveness of Islamic financial industry. Thus it is crucial to place strong focus on human capital development in embarking Islamic financial services encompassing the basic foundation namely; education. A prerequisite requirement for highly talented and skilled labor force is essential to maximize the opportunities presented by the evolving economic environment in the future. The objective of this study is to determine the issues faced by practitioners that initiate the need to undertake training and development courses as well as to identify the type of training required by current practitioners that affect performance. The main findings of the study can be more comprehensive and representative if more respondents from several banks that practices Islamic finance can be involved in validating the issue that is realizable for future study.